IBN RUSHD AS JURIST” AND HIS FATWĀ ON LEGAL CAPACITY - Fachrizal A. Halim (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2018)
Legal capacity is one of the major topics in Islamic law on personal status. The Qurʾān deals with this subject, for example in Q 4: 5-6. However, it only discusses the issue of legal capacity in relation to orphans and minors. Based on the loose Qurʾānic concept of orphans and minors, the jurists of the classical period attempted to understand what was meant by legal capacity in Islam and how ought to operated in a Muslim society. One of the most remarkable jurists who tackled this issue was Ibn Rushd (520/1126-595-1198). In his celebrated collection of fatwā, the Fatāwā Ibn Rushd, he explored the issue of legal capacity based on questions brought to him, who at a time sit as a qāḍī in Sevilla and Cordoba. Keywords: Averroes, legal, capacity, personal status, guardianship, Muslim Spain.